An efficient mobile grid scheme for service tracking in VANETs. (2018) - Dow, Chyi-Ren; Lee, Yu-Hong; Hwang, Shiow-Fen; Bui, Van-Tung
Intelligent transportation systems deployed on vehicular ad hoc networks (VANETs) are usually highly distributed and depend on metadata exchanging, data sharing and service tracking mechanisms. This study focused on the mobile grid scheme and service tracking protocol in VANETs. Our mobile grid scheme uses the characteristic of group mobility to increase grid structure flexibility and reduce maintenance costs. The tracking protocol is used to manage the service footprint information and continuously track the target service. Indicators manage the footprint of the service providers in their branches. Users can simply rely on the footprint information to locate target services. According to the experimental results, the mobile grid sequences effectively extended the service time and information was reliably shared. Our service tracking scheme is more efficient than other schemes in terms of success rate and service tracking time.